(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2015)
The “global” dimension of sport is, in the first instance, regulatory, and it embraces the whole complex of norms produced and implemented by regulatory sporting regimes at the international and domestic levels. These rules include not only private norms set by the International Olympic Committee (IOC) and by International Federations (IFs) but also “hybrid” public-private norms approved by the World Anti-Doping Agency (WADA) and international law (such as the UNESCO Convention Against Doping in Sport). Sports law, therefore, is highly heterogeneous, and, above all, it is not simply transnational, but actually “global”. This law represents an autonomous global legal system, which displays distinctive features such as the presence of some separation of powers (in particular quasi-judicial, with the strategic role played by the Court of Arbitration for Sport) and the development of relevant procedural principles (e.g. fairness and due process); and these principles operate both in rulemaking procedures (e.g. the adoption of the WADA Code) and in adjudicatory ones (e.g. for disciplinary measures). Finally, this global legal system is made up with several international regulatory regimes, both private – such as the Olympic movement – and hybrid public and private – such as the world anti-doping regime. The paper will deal in particular with this latter issue. The analysis will focus on the global administrative dimensions of sports regimes, together with their inter-institutional relationships and its legal implications for the public and private interaction.